2023
DOI: 10.1038/s41467-023-36207-7
|View full text |Cite
|
Sign up to set email alerts
|

Global vegetation resilience linked to water availability and variability

Abstract: Quantifying the resilience of vegetated ecosystems is key to constraining both present-day and future global impacts of anthropogenic climate change. Here we apply both empirical and theoretical resilience metrics to remotely-sensed vegetation data in order to examine the role of water availability and variability in controlling vegetation resilience at the global scale. We find a concise global relationship where vegetation resilience is greater in regions with higher water availability. We also reveal that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Additionally, LAI primarily influences AET/PET in these ecosystems through its indirect effect on soil moisture. Being an indicator of vegetation, LAI plays a key role in SW conservation (Jasechko et al, 2013; Smith & Boers, 2023). Studies have indicated that soil evaporation contributes more to actual ET when LAI is low (Knapp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LAI primarily influences AET/PET in these ecosystems through its indirect effect on soil moisture. Being an indicator of vegetation, LAI plays a key role in SW conservation (Jasechko et al, 2013; Smith & Boers, 2023). Studies have indicated that soil evaporation contributes more to actual ET when LAI is low (Knapp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the alpine meadow and P. euphratica ecosystems, the role of SW is particularly prominent (Figure 6). Soil moisture acts as the main reservoir for plant transpiration and surface evaporation (Gampe et al, 2021; Green et al, 2019), playing a crucial role in transporting water from the soil to the atmosphere (Forzieri et al, 2020; Smith & Boers, 2023). SW evaporation is the primary water loss in ecosystems (Humphrey et al, 2021), and it is also the most important water source for vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed abiotic legacies include altered biogeochemical cycles that affect nutrient availability, the carryover of soil water deficits from previous years, changes in ecosystem water relations, soil structure and even the loss of soil due to erosion (Austin et al., 2004; de Vries et al., 2016, 2023; Duniway et al., 2019; Kusch et al., 2022; Müller & Bahn, 2022; Munson et al., 2011; Reichmann et al., 2013; Robinson et al., 2016; Sala et al., 2012; Shen et al., 2016; Vilonen et al., 2022; White et al., 2004; Wiegand et al., 2004). Adding further complexity to understanding post‐drought dynamics, climatic conditions after drought will strongly affect the persistence of these legacies and thus the nature and pace of ecosystem recovery (Jiao et al., 2021; Kusch et al., 2022; Smith & Boers, 2023; Sun et al., 2022; Yao et al., 2023).…”
Section: Looking Forwardmentioning
confidence: 99%
“…To date, most studies have assessed grassland responses to drought (Gao et al, 2019; Luo et al, 2021), while studies investigating how grassland ecosystems recover from drought are less common (Griffin‐Nolan et al, 2018; Ingrisch & Bahn, 2018; Müller & Bahn, 2022; Sun et al, 2022; Zhou et al, 2022). However, drought legacies can influence grassland processes and functions for many years following severe drought (Broderick et al, 2022; De Boeck et al, 2018; Smith & Boers, 2023). Therefore, quantifying drought recovery and factors determining legacy effects of drought on grassland function and structure remains a major knowledge gap.…”
Section: Introductionmentioning
confidence: 99%